Evaluation of microalbuminuria in obesity phenotypes - Arzoo R Alagh; Samarth Shukla; Sourya Acharya; Sunita Vagha; Loveleen Dhingra (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Obesity is a universal health issue of the present time. Nearly 2 billion people were estimated to be either overweight or obese in 2020, with nearly 3.4 million deaths worldwide. Proteinuria is now widely known to be a significant predictor of renal pathologies including end-stage renal disease. This study aimed to assess the relationship between the presence of microalbuminuria (MA) in obese individuals. MATERIALS AND METHODS: This cross-sectional study was conducted among patients attending the outpatient department of Jawaharlal Nehru Medical College and Acharya Vinoba Bhave Rural Hospital, Sawangi (Meghe), Wardha. From the subjects meeting the study criteria, selected 150 individuals with BMI ≥ 25 that formed the obese group. Obese individuals were further subdivided as metabolic healthy obese (MHO) and metabolic abnormal obese (MAO) based on metablic syndrome criteria. From the non-obese patients (BMI≤25), one age and gender matched control was selected for each obese subject. All subjects were tested for MA by dipstick method. Data was analyzed using SPSS and Chi-square test was performed to test for statistical significance. RESULTS: The study reflected the association of MA in the groups studied. The metabolic abnormal obese group was noted as having the highest percentage of positive cases (53.7%) of MA, followed by the MHO group (31.3%). A significant association of prevalence of MA was seen in MHO and MAO obese individuals (P < 0.001). MA was present in the urine samples of 26 (31.3%) obese subjects in the MHO group, 36 (53.7%) in the MAO group, and 8 (5.3%) in the control population. CONCLUSION: Both MHO and MAO subgroups of obese individuals showed higher proportion of MA indicating adverse renal function. Therefore, primary prophylactic measures such as health education and lifestyle modification should be promoted for the obese to reduce their body weight and thereby possibly reduce the risk of future obesity-related renal complications.